Японський ляльковий театр бунраку - Литвин, А. О. (ХНУРЕ, 2020)
Having read this article you will know what is the hangs of traditional Japan puppet show Bunraku. Here is the material about history and pioneers of this art, descriptions of unique and racy puppeteer-led dolls captured in pictures with their puppeteer-masters.
Keywords: культурне розмаїття; українознавство; традиції